2017
DOI: 10.1038/s41598-017-08887-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory drugs suppress ultrasound-mediated mesenchymal stromal cell tropism to kidneys

Abstract: Mesenchymal stromal cells (MSC) are potential renal therapeutics. Clinically, results are mixed partly because MSC tropism to kidneys is minimal following infusion. Ultrasound augmentation of the renal microenvironment is becoming increasingly-important in renal MSC therapies. We demonstrated pulsed-focused-ultrasound (pFUS) increases enhanced homing permeability and retention of MSC in mouse kidneys. Here, we characterized the temporal proteomic response to pFUS in mouse kidneys and its association with MSC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…These discrepancies suggest that there are different molecular mechanisms by which pFUS operates, depending on ultrasound parameters. The studies by Burks et al show that pFUS transiently activates TNF-α and IL-1α expression in the sonicated tissue, which act through NF-κB signaling to drive cyclooxygenase-2 (COX2) activity; in turn, this promotes the expression of several homing factors and increases the local accumulation of MSCs, thus augmenting their therapeutic effect [43,44]. Our previous studies have shown, however, that pFUS can improve MSC therapy independently of improved homing [29].…”
Section: Discussionmentioning
confidence: 94%
“…These discrepancies suggest that there are different molecular mechanisms by which pFUS operates, depending on ultrasound parameters. The studies by Burks et al show that pFUS transiently activates TNF-α and IL-1α expression in the sonicated tissue, which act through NF-κB signaling to drive cyclooxygenase-2 (COX2) activity; in turn, this promotes the expression of several homing factors and increases the local accumulation of MSCs, thus augmenting their therapeutic effect [43,44]. Our previous studies have shown, however, that pFUS can improve MSC therapy independently of improved homing [29].…”
Section: Discussionmentioning
confidence: 94%
“…Parallel results have been achieved in the kidney, where pFUS created a similar chemical gradient without any physiological damage to the host tissue, and dramatically increased MSC homing (Ziadloo et al., 2012). Similar to muscle, pFUS causes initial activation of TNFα and IL-1α in the kidney, which drive signaling through the nuclear factor-κB and COX2 pathways (Burks et al., 2017). In a mouse model of cisplatin-induced AKI, pFUS + MSCs significantly enhanced kidney homing and clinical outcomes compared with MSCs alone (Burks et al., 2015).…”
Section: Modification Of Target Tissuementioning
confidence: 99%
“…For this study, production of the prostaglandins PGH 2 and PGE 2 were investigated serving as proxy indicators of microenvironmental changes. We have previously demonstrated that COX2 upregulation by NFκB is a critical component of the molecular signaling cascade within 4–6 h following pFUS at 4 MPa ( Tebebi et al, 2015 ; Burks et al, 2017 , 2019 ). While we have investigated COX2 expression in multiple studies, we have never investigated enzyme activity by quantifying metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Previous US studies characterized the molecular microenvironmental changes in tissues post-sonication and overwhelmingly observe increased expression of cytokines, chemokines, trophic factors and adhesion molecules (CAM) which would facilitate stem cell tethering and rolling across the activated endothelium followed by diapedesis into the parenchyma ( Liu et al, 2020 ). Several of our previous studies have investigated microenvironmental changes alone ( Burks et al, 2011 ) or in context of stem cell homing to skeletal muscle and kidney using 1 MHz pFUS at a peak negative pressure (PNP) of ∼4 MPa without microbubble (MB) infusions ( Ziadloo et al, 2012 ; Burks et al, 2013 , 2017 ; Tebebi et al, 2015 ). We have demonstrated that microenvironmental changes to facilitate stem cell homing require nuclear factor kappa B (NFκB) activation and subsequent cyclooxygenase-2 (COX2) upregulation ( Tebebi et al, 2015 ; Burks et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation